Permasalahan Keterlibatan Militer dalam Penegakan Protokol Kesehata - Theo Reynol Sandy; Ulfa Umayasari (Kybernan: Jurnal Studi Kepemerintahan, 2022)
The rise of conflicts that occur between the community and the apparatus during the pandemic, especially in the enforcement of health protocols, one of which relates to the involvement of military elements in the composition of the Covid-19 Task Force (Satgas). The involvement of the military is suspected to be the cause of the fading of the humanist image in the practice of enforcing health protocols. The continued involvement of the military without clear boundaries is feared to cause much bigger problems, including the weakening of civilian supremacy. The purpose of this study is to consider the position and limits of military involvement in the enforcement of health protocols in the community. The research method used is literature study analysis with a descriptive qualitative approach. Data was obtained from journals, books, and news. This study resulted in the finding that the involvement of military elements in the enforcement of health protocols needs further consideration. On the one hand, the meaning of the Covid-19 pandemic as a national epidemic that needs to get mutual attention from all parties is one of the reasons why the role of the military should be included. But on the other hand, it produces the potential for more serious problems. For this reason, it is necessary to set clear boundaries on the extent to which the military can be involved in the enforcement of health protocols in particular, and other civilian affairs in general.